Madrasah Principals’ Educational Management Strategies In Improving Graduate Quality - Ahmad Mujtahid Latif; Abdus Salam; Iman Subasman; Ade Aspandi; Atik Rosanti (MASI Mandiri Edukasi, 2026)
This study examines the strategies employed by madrasah principals in managing educational programs and enhancing the quality of graduates in Madrasah Diniyah Takmiliyah Awaliyah (MDTA). The research addresses the limited scholarly attention given to leadership practices in non-formal Islamic educational institutions, particularly regarding how principals manage educational programs to meet community expectations and improve graduate outcomes. This study aims to analyze the managerial strategies implemented by madrasah principals and to identify leadership characteristics that contribute to educational quality improvement. The study applied a qualitative research approach through observations, in-depth interviews, and documentation conducted at MDTA Uswatun Hasanah Harjamukti and MDTA Darul Fikr Lemahwungkuk from February 5 to 15, 2025. Data were analyzed descriptively to interpret leadership practices and educational management strategies implemented in both institutions. The findings reveal that graduate quality improvement is influenced by several managerial strategies, including curriculum development, student-centered learning activities, the application of appropriate teaching methods, teacher qualification standards, competency development programs, evaluation systems, and institutional collaboration. The study also identifies the IKLAS leadership framework, Innovative, Creative, Evaluative, Accommodative, and Selective, as a contextual leadership model that strengthens the effectiveness of educational program management in MDTA institutions. This study contributes to the development of leadership studies in non-formal Islamic education by offering a practicum.